Gendered constructions of school headship: Of Chivi district in Masvingo Province, Zimbabwe - Efiritha Chauraya; Clemence Dzingirai (MSU Press, 2023)
This article reports a study on gendered constructions of school leadership in Zimbabwean schools. Gendered constructions perpetuate inequality between females and males in educational leadership. The study uses an interpretive phenomenological analysis to establish the lived experiences of 15 senior women in Chivi district secondary schools. Of the 15 senior women leaders who participated in this research, ten were subjected to semi-structured interviews and five were subjected to a focus group discussion. Findings indicated that female teachers were hesitant to advance into school leadership because of gender stereotypes, female teachers perceived idealised leader, extrinsic normative constraints, and difficulties in managing women’s bodies when performing leadership roles. To involve senior women to change and go for leadership in education, the researchers recommended procedures to counteract the female teachers’ conscious and subconscious dispositions created by gendered constructions.